Clinical evaluation of sofosbuvir/ledipasvir in patients with chronic hepatitis C genotype 1 with and without prior daclatasvir/asunaprevir therapy. Issue 12 (6th May 2017) - Iio, Etsuko; Shimada, Noritomo; Takaguchi, Koichi; Senoh, Tomonori; Eguchi, Yuichiro; Atsukawa, Masanori; Tsubota, Akihito; Abe, Hiroshi; Kato, Keizo; Kusakabe, Atsunori; Miyaki, Tomokatsu; Matsuura, Kentaro; et al.
Abstract : Aim: This study explored treatment outcomes of sofosbuvir (SOF)/ledipasvir (LDV) therapy for chronic hepatitis C patients with and without prior daclatasvir (DCV)/asunaprevir (ASV) therapy. Methods: Overall, 530 Japanese patients who were infected with hepatitis C virus genotype 1 received SOF/LDV therapy for 12 weeks, and resistance‐associated variants (RAVs) in the hepatitis C virus non‐structural protein (NS)5A and NS5B regions were assessed at baseline and virological relapse by direct sequencing. Results: Sustained virological response (SVR) rates did not significantly differ between patients with and without NS5A Y93H/N (94.2% [113/120] vs. 97.7% [345/353]), but the SVR rate was significantly lower in patients with prior DCV/ASV therapy compared to those without (69.2% [18/26] vs. 98.4% [496/504], P  < 0.001). Among 26 patients with prior DCV/ASV therapy, the prevalence of NS5A multi‐RAVs (≥2) was similar between responders and non‐responders (61% [11/18] vs. 75% [5/8]), but all patients without RAVs achieved SVR. Multivariate analysis showed that prior DCV/ASV therapy and history of hepatocellular carcinoma were independently associated with treatment failure (odds ratio, 37.55; 95% confidence interval, 10.78–130.76; P  < 0.001 for prior DCV/ASV therapy; odds ratio, 4.42; 95% confidence interval, 1.09–18.04; P  = 0.03 for the history of HCC). All SOF/LDV failure patients ( n  = 8) with prior DCV/ASV treatment had two or more factors of cirrhosis, IL28B unfavorable genotype, and baseline NS5A multi‐RAVs. The multiple NS5A RAVs had increased but NS5B substitutions, C316N/A207T/A218S or L159F, had not changed at the time of relapse. Conclusions: Prior DCV/ASV therapy is associated with failure of SOF/LDV therapy due to multiple RAVs.